Impact Of Discharge Fertilizer Effluents On The Toxicological Profile Of Fish Harvested From A Receiving Creek In Okirika, Rivers State. - Kalu Igwe; Kelechi Uche; Uchechi Obasi (Diponegoro University, 2016)
The impact of fertilizer effluent discharge on toxicological profile of fish was studied by harvesting fish from Okrika creek which receives treated fertilizer effluent and analysing same for heavy metal (Lead Pb, Nickel Ni, Zinc Z and Copper Cu); Polycyclic Aromatic Hydrocarbon (PAH) and Total Petroleum Hydrocarbon (TPH) concentrations. Similar fish was harvested from Otamiri River which is far from any industrial activity and used as control. Heavy metals were analysed using Atomic Absorption Spectrophotometer while the PAH and TPH were analysed using Gas Chromatography. Result indicated unacceptable high values in most of the studied parameters with significantly higher (P<0.05) values; Pb (8.10±0.02 mg/kg), Ni (1.24±0.12 mg/kg), Zn (22.82±0.13 mg/kg), Cu (2.79±0.16 mg/kg), TPH (1.24±0.01 mg/kg). PAH indicated no significant difference (P>0.05) with value 0.003±0.01 mg/kg. Result indicates an unacceptable high level of these metals in the fish tissue which is of great concern to consumers and could reflect the level of pollutant in the effluent. The company is thus advised to treat their effluents properly and government ensures compliance.